EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIFJIGSAW DALAM MENINGKATKAN HASIL BELAJAR IPS DI SMP - Marsita Yanti; Achmadi Achmadi; Okianna Okianna (Universitas Tanjungpura, 2019)
AbstractThis research aimed to determine the effectiveness of jigsaw cooperative learning model with the use of conventional learning model. The form of this research was a quasi-experimental form with a nonequivalent control group design. The tool of data collections in this research were the test results in the form of multiple choice and observation sheets. The results of normality test in this research were the post-test score in the experimental class was 0,200 and the control class was 0,110. This showed that the significant post-test data of the experimental class and the control class were normally distributed, meaning that both data were >0,05. Then, in the experimental class after the treatment by using the Jigsaw cooperative learning model has increased the average value, from the average value of examination before being given treatment that was 56,87 into the average value of post-test was 87,85. The experimental class also increased the percentage of completeness from 36,33% to the percentage of post-test completeness to 100%. Thus, it can be concluded that learning by using the jigsaw cooperative learning model with the learning material about the interaction between ASEAN countries in class VIII of SMP N 21 Pontianak showed very effective criteria for improving student learning outcomes, with a difference in the percentage of completeness 90,67% and with the effect size value of 0,85. Keywords: Cooperative Jigsaw, Effectiveness, Learning Model